Rainfed agriculture in Ethiopia: a systematic review of green water management pathways to improve water and food security - Teferi, Ermias; Kassawmar, Tibebu; Bewket, Woldeamlak; Zeleke, Gete; Ayele, Gebiaw T.; O’Donnell, Greg; Walsh, Claire (Frontiers in Agronomy, 2025)
It is widely acknowledged that the world is currently experiencing an unprecedented water shortage, with agriculture being a crucial contributor. This paper presents a synthesis of available evidence, identify knowledge gaps, and make a state-of-the-art synthesis on green water management in Ethiopia. A systematic review methodology was implemented, encompassing the compilation and analysis of peer-reviewed and gray literature. The paper demonstrates that rainfed agriculture, which relies on “green water” (soil moisture from rainfall), accounts for 80% of cultivated land and 60-70% of global crop production. However, green water management has not received adequate attention in water policy and land rehabilitation programs in Ethiopia, where irrigation is limited. The analysis reveals a large yield gap and water productivity gap for major crops like maize, sorghum, and wheat in Ethiopia’s rainfed agriculture. Increasing crop yields through better soil, water, and crop management practices can significantly improve water productivity, offering “windows of opportunity” to enhance food and water security. Thus, a paradigm shift from the traditional narrow focus on soil erosion control towards an integrated green-blue water management approach in water and agricultural policies and programs is urgently required. Increased investments and expertise in green water management at the government level are crucial. Optimizing the use of green water resources in rainfed farming can also unlock Ethiopia’s export potential while improving domestic water and food security through strategic virtual water trade. In conclusion, the review highlights unlocking the potential of green water resources through targeted investments and policy support for rainfed agriculture can significantly contribute to Ethiopia’s water and food security objectives in a cost-effective and environmentally sustainable manner.